Durability of Accoya Wood in Ground Stake Testing after 10 Years of Exposure in Greece - George I. Mantanis (Polymers, 2020)
In this research, acetylated wood (Accoya) was tested in ground contact in central Greece. After ten years of exposure during a ground stake test, acetylated pine wood (Pinus radiata) stakes, with a 20% acetyl weight gain, were completely intact and showed no visual decay (decay rating: 0). However, the key mechanical properties of Accoya wood, that is, modulus of elasticity (MOE) and modulus of rupture (MOR) after 10 years of ground contact, were significantly reduced by 32.8% and 29.6%, respectively, despite an excellent visual result since no evidence of fungal attack was identified. This contradiction could possibly indicate that the hallmarks of decay, i.e., brown-rot decay of acetylated wood can be the significant loss of mechanical properties before decay is actually visible.